1998
DOI: 10.1093/carcin/19.1.141
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genotoxicity and DNA adduct levels in the liver of rats treated with safrole

Abstract: The induction of chromosome aberrations, sister chromatid exchanges (SCEs), and the formation of DNA adducts was studied in hepatocytes of F344 rats exposed in vivo to safrole. Hepatocytes were isolated 24 h after a single dose of safrole or five repeated doses (once a day) by gastric intubation and allowed to proliferate in Williams' medium E supplemented with epidermal growth factor. Cells were fixed after 48 h in culture. Safrole-DNA adducts were detected by a nuclease P1-enhanced 32P-post-labeling assay in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 27 publications
1
32
0
2
Order By: Relevance
“…While estragole, methyleugenol, safroleand anethole haveproved to be hepatotoxic, genotoxic and 312 carcinogenic, the genotoxic and possibly carcinogenic potential of myristicin at equivalent doses is 313 not to be expected .Dose-dependent formation of protein and DNA adducts in liver [22][23][24][25][26][27][28][29] was 314 observed with allyl alkoxy benzenes. Although DNA adducts in the liver of CD1 female mice were 315 isolated, the binding of myristicin to mouse-liver DNA was weaker than those of other compounds 316 such as safrole, estragole, and methyleugenol 10 .…”
Section: Micronucleus Assay 278mentioning
confidence: 99%
“…While estragole, methyleugenol, safroleand anethole haveproved to be hepatotoxic, genotoxic and 312 carcinogenic, the genotoxic and possibly carcinogenic potential of myristicin at equivalent doses is 313 not to be expected .Dose-dependent formation of protein and DNA adducts in liver [22][23][24][25][26][27][28][29] was 314 observed with allyl alkoxy benzenes. Although DNA adducts in the liver of CD1 female mice were 315 isolated, the binding of myristicin to mouse-liver DNA was weaker than those of other compounds 316 such as safrole, estragole, and methyleugenol 10 .…”
Section: Micronucleus Assay 278mentioning
confidence: 99%
“…However, some toxicological studies on animals have revealed that safrole is a weak hepatocarcinogen, genotoxic, and a transplacental carcinogen [6][7][8]. In addition, methyleugenol has been demonstrated to be carcinogenic and genotoxic [9][10][11].…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…The unstable sulfate ester is anticipated to hydrolyse to form a reactive electrophilic intermediate (carbonium ion or quinonium cation), which binds to proteins and DNA. The formation of protein and DNA adducts in liver is dose dependent (Drinkwater et al, 1976;Swanson et al, 1981;Miller et al, 1982Miller et al, , 1983Boberg et al, 1983;Gardner et al, 1995Gardner et al, , 1996Daimon et al, 1998). Sulfate inhibition studies and in vivo-in vitro unscheduled DNA synthesis (UDS) assays of myristicin, elemicin, estragole, methyl eugenol and the 1 -hydroxy metabolites of estragole and methyl eugenol (Boberg et al, 1983;Caldwell et al, 1992;Hasheminejad & Caldwell, 1994) provide additional evidence that the sulfate ester of the 1 -hydroxy metabolite is the principal intoxication metabolite in animals.…”
Section: O-demethylenationmentioning
confidence: 99%
“…Dose-dependent formation of safrole-DNA adducts has been studied in rats (Daimon et al, 1998). Male Fischer rats were given either single oral doses of 0, 1, 10, 100, 250 or 500 mg safrole/kg bw or five successive daily doses of 62.5, 125 or 250 mg safrole/kg bw.…”
Section: Dna Adducts (A) Rodent Dna Adductsmentioning
confidence: 99%